Digging through Databases—A Case Study of Iron Age Sites in Finland by Generating and Analysing Keywords - Johanna Roiha; Markus Holopainen (Heritage, 2023)
The primary purpose of this study is to open the discussion of FAIR principles in Finnish archaeology. This topic has not yet been actively discussed in Finnish archaeology. In this study, we were testing whether adding keywords could increase the reusability of the Register of Ancient Sites, as the reusability level of the current register is low. The case study focuses on creating an overview of the Iron Age sites in the Itä-Häme area. Keywords were added for all of the 585 archaeological sites in the study area, based on field reports and find catalogues. After giving keywords to all of the sites, it was possible to make queries from the register and form a new, more detailed overview of the Iron Age sites in the Itä-Häme area. Our study revealed mistakes and ambiguities in the register, but adding keywords increased its reusability. However, it cannot solve the main issue: basic research has not been carried out extensively enough in Finland. Based on the overview, it can be seen that Itä-Häme was an active and important area in the Iron Age, and an especially meaningful possible new site type was identified; however, more research in this area is needed.